Identificación de microorganismos mediante la captura en dos terrazas agrícolas en el Campus Salache, Latacunga, Cotopaxi. - Sánchez Riofrio, Christian David (2022)
The current reserch was made at the Cotopaxi Technical University, Salache sector, at a 2747 height m.a.s.l. with 78° 37'28'' west longitude and 0° 59' 60'' south latitude, with the aim at identifying microorganisms by capturing on two agricultural terraces. It was applied a statistically hypothesis to assess means, throungh a T test and to make a comparison two bench terraces, which it is determined, if there is a significant difference. To statistically assess the got data in the experiment, it was made a soil fungi and bacteria quantification, subsequently, it was used a T test and the significant variance sourses relationship. The research expressed the following results: the agricultural terrace number eight had greater significance, since they produced the microorganisms colonization best results based on Trichoderma, Aspergillus, Beauveria, Alternaria, Fusarium and Botrytis, getting 77.93% colonization percentages in to agricultural terrace eight and with 60.18% for the terrace seven with regard to fungi with media crop agar (PDA) of potato dextrose, thus also, having a colonization high percentage of the localized bacteria from genera Bacillus, Micrococcus and Clostidium of 171, 18% for agricultural terrace number eight and 130.31% for agricultural terrace seven with media crop agar (PCA) plate count.